2011
DOI: 10.1111/j.1365-2559.2011.03787.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between invasive pattern and immunophenotypic alterations in endocervical adenocarcinoma

Abstract: Endocervical adenocarcinomas that demonstrate an infiltrative growth pattern show immunophenotypic changes consistent with EMT. Frequently, these are accompanied by a morphological alteration in the tumour cells and the changes exhibit a specific micro-anatomical distribution. Epithelial-mesenchymal transition may represent an important mechanism in the progression of some endocervical neoplasms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 40 publications
(101 reference statements)
3
17
0
Order By: Relevance
“…In this study, we investigated whether 2 additional markers, cyclin D1 and PAX2, might be of diagnostic value in this setting. Nevertheless, the expression of cyclin D1 in MGH is consistent with a non-neoplastic and non-HPV-related process, as most ACIS lesions and invasive endocervical adenocarcinomas are cyclin D1-negative (29,41). Herein, in a larger series, we found that MGH and atypical MGH were consistently cyclin D1-positive, but that staining in the former lesions was variable in extent and was focal in almost half of the cases.…”
Section: Discussionsupporting
confidence: 48%
“…In this study, we investigated whether 2 additional markers, cyclin D1 and PAX2, might be of diagnostic value in this setting. Nevertheless, the expression of cyclin D1 in MGH is consistent with a non-neoplastic and non-HPV-related process, as most ACIS lesions and invasive endocervical adenocarcinomas are cyclin D1-negative (29,41). Herein, in a larger series, we found that MGH and atypical MGH were consistently cyclin D1-positive, but that staining in the former lesions was variable in extent and was focal in almost half of the cases.…”
Section: Discussionsupporting
confidence: 48%
“…In contrast, uVIN showed consistently reduced cyclin D1 reactivity despite the increase in Ki67 labelling thus indicating discordant expression of these proliferation-associated proteins. Similar findings have been reported in cervical squamous and glandular intraepithelial lesions and in HPV-associated neoplasms of the head and neck,13 14 27–29 and this most likely reflects HPV-related disruption of intracellular feedback loops involving the retinoblastoma protein. Our findings suggest that the reduced expression of cyclin D1 could also be used diagnostically in conjunction with ‘positive’ staining markers such as p16 protein and Ki67 to support a diagnosis of uVIN, and to distinguish the basaloid and differentiated subtypes of VIN.…”
Section: Discussionsupporting
confidence: 83%
“…However, it should be noted that the staining patterns of p16-positive and p16-negative SCCs were not completely uniform suggesting that different invasive pathways may also occur within each tumour subgroup. Previously, we have suggested that the localised upregulation of proteins such as cyclin D1 and fascin occurs during epithelial–mesenchymal transition (EMT),14 18 21 24 a process that is considered important in the process of invasion in many common cancers. Interestingly, Rodrigues et al recently reported decreased β-catenin and increased vimentin expression at the invasive front of vulvar SCCs consistent with EMT 42.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported localised immunophenotypic alterations, specifically the novel expression of cyclin D1 and vimentin with corresponding loss of E-cadherin and β-catenin, in a proportion of cervical adenocarcinomas 7–9. These changes were most conspicuous within the infiltrative component of the tumours, typically situated towards the deep tumour margin (invasive front), and on the basis of these findings we suggested that the features could represent an epithelial–mesenchymal transition within a subgroup of these tumours 9. Nevertheless, relatively little is known of the factors that control or influence the invasive growth patterns of endocervical adenocarcinomas.…”
Section: Introductionmentioning
confidence: 68%